1995
DOI: 10.1002/mrm.1910330103
|View full text |Cite
|
Sign up to set email alerts
|

Migration and Accumulation of Silicone in the Liver of Women with Silicone Gel‐Filled Breast Implants

Abstract: 1H NMR localized spectroscopy (STEAM), combined with echocardiography (ECG), respiratory gating, and water and fat suppression, was used to quantify silicone concentrations in the liver of women with silicone gel-filled breast implants. Localized spectroscopy was performed on 15 patients with silicone gel-filled breast prostheses and on eight volunteers with no implants. The 1H spectra in the liver of patients showed silicone resonances from 0.3 to -0.8 ppm, attributable to protons in the methyl groups of sili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
33
0

Year Published

1998
1998
2002
2002

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 61 publications
(34 citation statements)
references
References 31 publications
1
33
0
Order By: Relevance
“…Using the data of Utell et al (11), we exposed subjects to 10 ppm D 4 by inhalation for 1 hr. This exposure period consisted of 10 min rest, 10 min exercise, 20 min rest, 10 min exercise, and finally 10 min rest before the D 4 inhalation was terminated.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Using the data of Utell et al (11), we exposed subjects to 10 ppm D 4 by inhalation for 1 hr. This exposure period consisted of 10 min rest, 10 min exercise, 20 min rest, 10 min exercise, and finally 10 min rest before the D 4 inhalation was terminated.…”
Section: Discussionmentioning
confidence: 99%
“…Residual LMWS ranged from 0.2 to 2% by weight for the silicone gel and 0.01% to 0.1% for the silicone envelope (1.04-10.4 mg) (5)(6)(7)(8)(9). Numerous studies have documented the migration of significant amounts of LMWS out of breast implants into surrounding breast tissues and to the liver (8)(9)(10)(11). This would add to the dermal or inhalation exposures from personal care products in a typical woman.…”
Section: Hoan-my Do Luu and Joseph C Huttermentioning
confidence: 99%
See 1 more Smart Citation
“…The bleeding of PDMS through the implant envelope has been associated with the formation of thicker capsules and capsule contracture (7)(8)(9). Studies have also found that silicone can migrate from the site of implant or injection to distant regions such as the liver, joints, and lymph nodes (10)(11)(12)(13)(14). Although there is no established connection between exposure to silicone and connective tissue diseases (15)(16)(17)(18)(19), the hypothesis that silicone breast implants may be associated with autoimmune disorders has increased the interest in understanding and characterizing silicone and its interaction with tissues.…”
mentioning
confidence: 97%
“…The steroid could be stopped for as long as 15 days, the leg problems would then recur. Abdominal and thigh MRI scans were performed to detect further spread of silicone [5,18].…”
mentioning
confidence: 99%